2007
DOI: 10.1088/0957-0233/18/11/022
|View full text |Cite
|
Sign up to set email alerts
|

Radiation thermometry applied to temperature measurement in the cutting process

Abstract: Temperature measurement of cutting tools used in machining processes has great technological importance, and it is interesting in a large number of industrial applications because wear is directly related to this variable. The influence of emissivity on the temperature measurement using radiation thermometers and the dependence of the measured temperature on the emissivity as a function of the surface roughness and the oxidation state is studied in this paper. Emissivity is measured using the direct radiometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitysupporting
confidence: 47%
See 3 more Smart Citations
“…8), 10) and 11). As pointed out above, obvious oscillations of normal spectral emissivity appears only at the first several min from the heating start in this work, whereas those reported in the literature 2,[8][9][10][11]14) appeared at very different heating times, typically from several seconds to an hour in the oxidizing surroundings.…”
Section: Strong Oscillation Of the Normal Spectral Emissivitysupporting
confidence: 47%
“…© 2015 ISIJ also by averaging the three pieces of specimens. Furthermore, we can employ the following equation 2) to estimate the temperature uncertainty contributed only by the surface oxidization, ..... (12) Where c2, with a value of 14 388 μm·K, is the second constant of Planck radiation law.…”
Section: Uncertainty Of Normal Spectral Emissivity Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The pyrometer utilized a single wavelength for measurement, which was deliberately chosen to minimize error (1 mm) [19]. The measurements were corrected for emissivity in the internal software of the pyrometer controller and a value of 0.7 was chosen for emissivity based on evaluation of the literature [20]. Error calculations were performed to quantify the impact of using an incorrect value for the emissivity, and it was shown that at 1600 8C and a wavelength of 1 mm the maximum error was 122 8C (7.7%), while at 1000 8C it was only 56 8C (5.6%).…”
Section: Methodsmentioning
confidence: 99%